Pediatric tele-coaching fidelity evaluation: Feasibility, perceived satisfaction and usefulness of a new measure - Ogourtsova, Tatiana; Majnemer, Annette; Brown, Amelie; Filliter, Helen Jillian; Wittmeier, Kristy; Hanson, Jessica; O’Donnell, Maureen (Frontiers in Rehabilitation Sciences, 2023)
Background: To promote and ensure coaches’ fidelity in delivering an online health coaching program to parents of children with suspected developmental delay, we developed and implemented a novel coaching fidelity rating tool, CO-FIDEL (COaches Fidelity in Intervention DELivery). We aimed to 1) Demonstrate CO-FIDEL’s feasibility in evaluating coaches’ fidelity and its change over time; and 2) Explore coaches’ satisfaction with and usefulness of the tool. Methods: In an observational study design, coaches (n=4) were assessed using the CO-FIDEL following each coaching session (n=13-14 sessions/parent-participant) during the pilot phase of a large randomized clinical trial involving eleven (n=11) parent-participants. Outcome measures included subsections’ fidelity measures, overall coaching fidelity, and coaching fidelity changes over time analyzed using descriptive and non-parametric statistics. In addition, using a four-point Likert Scale and open-ended questions, coaches were surveyed on their satisfaction and preference levels, as well as facilitators, barriers, and impacts related to the use of CO-FIDEL. These were analyzed using descriptive statistics and content analysis. Results: One hundred and thirty-nine (n=139) coaching sessions were evaluated with the CO-FIDEL. On average, overall fidelity was high (88.0 ± 6.3 to 99.5 ± 0.8%). Four coaching sessions were needed to achieve and maintain a ≥ 85.0% fidelity in all four sections of the tool. Two coaches showed significant improvements in their coaching skills over time in some of the CO-FIDEL sections (Coach B/ Section 1/ between parent-participant B1 and B3: 89.9 ± 4.6 vs. 98.5 ± 2.6, Z=-2.74, p=0.00596; Coach C/ Section 4/ between parent-participant C1 and C2: 82.4 ± 7.5 vs. 89.1 ± 4.1, Z=-2.66; p=0.00758), and in overall fidelity (Coach C, between parent-participant C1 and C2: 88.67 ± 6.32 vs. 94.53 ± 1.23, Z=-2.66; p=0. 00758). Coaches mainly reported moderate-high satisfaction with and usefulness of the tool, and pointed out areas of improvement (e.g., ceiling effect, missing elements). Conclusions: A new tool ascertaining coaches’ fidelity was developed, applied, and shown to be feasible. Future research should address the identified challenges and examine the psychometric properties of the CO-FIDEL.